2012
DOI: 10.1590/s0103-84782012001100010
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento vegetativo e reprodutivo em gladíolo

Abstract: IIIDesenvolvimento vegetativo e reprodutivo em gladíolo Vegetative 'Peter Pears', 'Sunset', 'T704', 'Traderhorn', 'Rose Supreme' and 'Jester', and another

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 8 publications
1
28
0
11
Order By: Relevance
“…No experimento 2, os valores absolutos de temperatura máxima e de temperatura mínima do ar foram de 39,2ºC, em 1/2/2013, e -0,8ºC em 25/7/2013, respectivamente. A exposição das plantas de gladíolo a diferentes temperaturas do ar é importante para o teste do conceito de antocrono, uma vez que a velocidade de abertura dos floretes pode ser dependente da temperatura do ar, assim como ocorre para o filocrono (Wilhelm & McMaster, 1995;Streck et al, 2012).…”
Section: Resultado E Discussãounclassified
See 1 more Smart Citation
“…No experimento 2, os valores absolutos de temperatura máxima e de temperatura mínima do ar foram de 39,2ºC, em 1/2/2013, e -0,8ºC em 25/7/2013, respectivamente. A exposição das plantas de gladíolo a diferentes temperaturas do ar é importante para o teste do conceito de antocrono, uma vez que a velocidade de abertura dos floretes pode ser dependente da temperatura do ar, assim como ocorre para o filocrono (Wilhelm & McMaster, 1995;Streck et al, 2012).…”
Section: Resultado E Discussãounclassified
“…Entre eles, destaca-se o termo filocrono, que foi utilizado pela primeira vez por Bunting & Drennen (1966) e é definido como o intervalo entre o aparecimento de folhas sucessivas em uma haste ou colmo. Atualmente este termo é amplamente utilizado no meio científico e acadêmico para descrever e compreender o desenvolvimento foliar de poáceas (Wilhelm & McMaster, 1995;Streck et al, 2007;Rosa et al, 2009) e de outras espécies (Dellai et al, 2005;Schuh et al, 2005;Dalmago et al, 2013), inclusive no gladíolo (Streck et al, 2012). Além do filocrono, outros termos utilizados são: plastocrono (Erickson & Michelini, 1957), primeiramente definido como o intervalo entre a formação de dois entrenós sucessivos e, posteriormente, como o intervalo de tempo entre a iniciação de primórdios sucessivos no ápice meristemático (Esau, 1965); e auxocrono (Hancock & Barlow, 1960), período entre estádios comparáveis de folhas sucessivas.…”
Section: Introductionunclassified
“…Air temperature is the main meteorological variable that affects the gladiolus developmental Muttoni et al cycle (STRECK et al, 2012), with three cardinal temperatures, the lower base (Tb), optimum (Tot) and upper base (TB) temperatures (YAN & HUNT, 1999). The Tb and TB temperatures represent, respectively, the temperatures below and above which plant development is absent or negligible, and Tot is the temperature at which the plant development rate is at the maximum (BONHOMME, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…STRECK et al (2012) reported a lengthening of the crop cycle at lower temperatures and reduction when the temperatures rise. SCHWAB et al (2015) formulated the phenological scale for gladiolus in which four phases are evident in the developmental cycle: dormancy phase, sprouting phase (from filiform roots appearance to sheaths appearance), vegetative phase (from emergence of the first leaf tip to emergence of the final leaf tip on the stem) and reproductive phase (from heading to plant senescence).…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, the vegetative phase can be understood as the result of the accumulation of phyllochron units, which are considered the building blocks of vegetative development. The phyllochron concept has been widely applied to annual and perennial crops (Streck et al, 2007;Rosa et al, 2009;Streck et al, 2012;Costa et al, 2014;Martins et al, 2014;Rodrigues et al, 2014;Davidson et al, 2015), and genetic and environmental factors that affect the phyllochron, as temperature, soil moisture, and photoperiod, have also been identified (Kirby, 1995). However, concerning the reproductive phase, less effort has been dedicated to describe flower development, especially with regard to the flower opening rate on inflorescences.…”
Section: Introductionmentioning
confidence: 99%